CARIPAL TUNNEL SYNDROME IN PATIENTS WITH FIBROMYALGIA SYNDROME - Mehmet Tosun; Haşim Çakırbay; Cavit Boz; Mustafa Güler (Archives of Rheumatology, 2002)
Fibromyalgia syndrome (FMS) and carpal tunnel syndrome (CTS) are two diseases that cause symptoms like pain, numbness, tingling, stiffness and subjective swelling in upper extremities. Because some symptoms are common in these two conditions, they can easily be mistaken for each other and this leads to misdiagnosis. In this study 28 patients diagnosed as FMS according to American Collage of Rheumatology (ACR) criteria were compared to 30 healthy controls on the grounds of median nerve conduction rate as measured by the standard neurophysiologic methods. Findings congruent with CTS have been obtained in the patient group for 3 cases bilaterally and one left and one right unilaterally, totally 8 extremities; in healthy controls same findings were obtained in 1 case bilaterally and 1 unilaterally, totally in 3 extremities. There was no statistically significant difference between the two groups (p>0.05).